Enteral nutrition training for nurses - Abd Kadir, Nor Syahiza; Mohd Fahmi Teng, Nur Islami; Ahmad Sharoni, Siti Khuzaimah; Kamarul Zaman, Mazuin; Mohd Fadzil, Suhaiza (UiTM Press, 2026)
The Enteral Nutrition Training for Nurses Module Booklet is a comprehensive guide designed to equip nursing professionals with the essential knowledge, practical skills, and confidence to deliver safe and effective enteral nutrition (EN) care. Covering fundamental principles, indications, tube types, formula selection, administration techniques, and monitoring, this module integrates evidence-based practices with key aspects of EN. It also addresses troubleshooting common complications and maintaining patient safety. Developed to support competency-based learning, the module serves as both a training resource for new nurses and a reference tool for experienced practitioners, ensuring optimal patient outcomes in enteral feeding.